Estimasi Sumberdaya Terukur Batukapur pada Area Bukit Tajarang dengan Menggunakan Metode Indicator Krigging di Tambang Quary PT. Semen Padang, Sumatera Barat - Mhd Zanil; Dedi Yulhendra (Departemen Teknik Pertambangan FT UNP, 2020)
Abstract. PT. Semen Padang is located in Indarung Village, Lubuk Kilangan Subdistrict which is 14 KM from the center of Padang City with a height of + 200 m above sea level is one of the companies engaged in the cement industry. Reserve calculation is an important work, the responsibility is in evaluating a mining project. All technical decisions are very dependent on the work. In this study, calcareous reserves will be calculated based on the cut-off grade of each material. In each of these materials there are levels of SiO2, Al2O3, CaO and MgO. In calculating the limestone reserves contained in the Tajarang Hill area, this was done using geostatistical techniques. This geostatistics uses the estimation method while still based on the model. The method that will be used in geostatistics is the indicator krigging method. The IK estimation method does not use the assumption of a normal (free) distribution, and still takes into account the outlier (high levels), so that it can be applied to the estimation of limestone reserves. The IK method is based on the concept of probability. Data is converted into indicators with zero (0) and one (1) value relative to a limit level (discriminator). The purpose of the IK assessment is to estimate the probability at various levels of a predetermined limit. From the results of calculation of limestone resources using the krigging indicator method based on the cut-off grade of PT. Semen Padang obtained the amount of limestone resources of 36,764,700 m 3 or 97,426,455 tonsKeywords: Reserve calculation, cut off grade, geostatistics, indicator krigging, and probabilistic